One-Pot Synthesis of Polysubstituted 3-Amino-2-oxo-2,7-dihydro-1H-azepines - Liao, Shengrong; Qin, Chun; Yao, Peifen; Li, Jinsheng; Zhou, Xuefeng; Wang, Junfeng; Huang, Zhishu; Liu, Yonghong (Synthesis, 2014)
A facile and efficient synthesis of novel seven-membered heterocyclic derivatives containing 3-aminoazepan-2-one backbone is described using 1,4-protected piperazine-2,5-diones and alkynes as starting materials. The reaction may undergo Michael addition, unusual nucleophilic attack to an amide group, and keto–enol tautomerization. The reaction showed different reactivity when using substrates with different protecting groups: it had higher efficiency when using either alkanoyl-protecting group with cesium carbonate as the base, or benzoyl-protecting group with triethylamine as the base, but no reaction when using benzyl or allyl protecting groups with a variety of bases (Et3N, DBU, K2CO3, Cs2CO3, KHCO3, CsHCO3, and KOt-Bu).
Keywords: alkyne; 3-aminoazepan-2-one; Michael addition; piperazine-2,5-dione; protecting groups